OPTIMIZATION OF TCS3200 COLOR SENSOR UTILIZATION IN THE DEVELOPMENT OF AN AUTOMATED SYSTEM FOR COFFEE BEAN SORTING BASED ON DISTANCE DIFFERENCES: OPTIMISASI PEMANFAATAN SENSOR WARNA TCS3200 DALAM PENGEMBANGAN SISTEM OTOMATIS UNTUK PEMILAHAN BIJI KOPI BERDASARKAN PERBEDAAN JARAK - Hanum Puji Pangesti; Hadi Nasbey; Haris Suhendar (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
The growing demand for high-quality coffee beans has driven the development of automated systems for coffee bean sorting. A critical component in such systems is the color sensor, which provides accurate information to optimize its usage in coffee bean sorting. This study tested the TCS3200 color sensor to optimize its application in the design of an automated coffee bean sorting system based on distance variations. The methodology involved identifying parameters affecting measurement accuracy and adjusting sensor parameters to respond to variations in color using three different colored papers. The sensor's distance was tested within a range of 1 cm to 20 cm, with increments of 0.5 cm. The results indicated that the optimal sensor distances were 16.5 cm, 7.5 cm, and 15 cm for the three different object colors, with an object size of 14.8 cm x 21 cm. These findings will be applied to the development of an automated coffee bean sorting system using Arduino Uno and the TCS3200 color sensor.